Evaluating the recycling effects on 316L stainless steel powder in LPBF and establishing qualification benchmark for recycled powder - Song, Zikang (Nanyang Technological University, 2025)
This study is sponsored by Entegris Asia, which evaluates the impacts of recycling 316L stainless steel powders in laser powder bed fusion (LPBF), a critical additive manufacturing technique. It focuses on how recycling influences key powder characteristics such as morphology, particle size distribution (PSD), flowability, and tap density, which are essential for consistent manufacturing performance. In experimental design, the tap density was measured by using tap density analyzer, flowability was measured by hall flowmeter and Morphologi 4 imaging system was used to measure morphology and particle size distribution. Key findings reveal that recycled powders undergo morphological changes, including an increase in irregular particles, which slightly impact flowability and packing density. PSD shows a gradual coarsening trend, with fewer fine particles due to consumption during the melting process. However, effective sieving mitigates these issues by removing oversized and irregular particles. The study demonstrates that recycled powders can achieve acceptable performance levels for LPBF applications with proper quality control measures. Tap density and flowability remain stable after initial recycling, while morphology and PSD stabilize with continued recycling cycles. These results underscore the viability of reusing powders to reduce costs and improve sustainability in additive manufacturing. Recycling contributes significantly to cost efficiency and waste reduction without compromising product quality. Future research should focus on optimizing recycling processes, such as advanced sieving and re-spheroidization techniques, to enhance powder consistency and broaden its industrial applications.